2018
DOI: 10.1002/ajcp.12227
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Neighborhood Disadvantage and Individual Social Support on Frequency of Alcohol Use in Youth Living with HIV

Abstract: Youth living with HIV (YLH) experience multiple disease-related stresses along with the same structural and developmental challenges faced by their uninfected peers; alcohol use among YLH represents a risk behavior by virtue of potential effects on youth health and increased likelihood of engaging in unprotected sex while drinking alcohol. Research aimed at better understanding the interplay of individual- and neighborhood-level influences on alcohol use for YLH is needed to inform interventions. This study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Our findings contribute to limited literature inversely linking social support to substance use in marginalized populations ( Averna & Hesselbrock, 2001 ; Brick et al, 2018 ; Buttram, Kurtz, & Surratt, 2013 ), including mixed results ( Spohr, Suzuki, Marshall, Taxman, & Walters, 2016 ). Although 30-day alcohol use and SPS in Sample 1 were significantly correlated in the opposite direction from what was hypothesized, this is not necessarily at odds with previous findings.…”
Section: Discussionsupporting
confidence: 60%
“…Our findings contribute to limited literature inversely linking social support to substance use in marginalized populations ( Averna & Hesselbrock, 2001 ; Brick et al, 2018 ; Buttram, Kurtz, & Surratt, 2013 ), including mixed results ( Spohr, Suzuki, Marshall, Taxman, & Walters, 2016 ). Although 30-day alcohol use and SPS in Sample 1 were significantly correlated in the opposite direction from what was hypothesized, this is not necessarily at odds with previous findings.…”
Section: Discussionsupporting
confidence: 60%
“…Higher social support is associated with lower alcohol consumption and problems (Groh et al, 2007; Peirce et al, 2000), particularly during stressful periods (Steptoe et al, 1996). Social support is thought to be protective against alcohol use and problematic drinking by providing greater social control and/or buffering the effects of stressful events, and it is also thought to reduce individuals’ likelihood of drinking to cope (Brick et al, 2018; Humphreys et al, 1999). High social support from family, romantic partners, and friends has been shown to be negatively associated with alcohol use problems (Jarnecke & South, 2014).…”
Section: Sensation Seeking As Intermediate Phenotype Linking Genetic ...mentioning
confidence: 99%
“…Findings on the relationship between social support and alcohol use remain equivocal. While some studies among PWH found no association between social support and alcohol use, other studies with PWH have found greater social support to be associated with greater unhealthy drinking [31][32][33][34]. Little is known about the extent to which social support modifies the relationship between IPV and mental health among PWH.…”
Section: Introductionmentioning
confidence: 99%